Cataract and genetic diseases - Kozik, Mateusz; Skalska-Dziobek, Nina; Małagocka, Weronika; Rozpłoch-Sapa, Maria; Chybowska, Karolina; Orłowski, Mateusz; Naruszewicz, Maria; Cetnarowski, Przemysław; Midro, Aleksandra; Zagórski, Karol (Quality in Sport, 2024)
Despite the decreasing number of cases, cataract is still the leading cause of visual impairment and blindness worldwide. The search for the causes of this disease, its risk factors and the relationship with systemic diseases is the subject of many studies and attracts the attention of scientists around the world. One of the most common cause of cataract and probably the most frequently reported in the literature, is aging. Other commonly described causes of cataracts are external factors and acquired diseases. Although genetic diseases are not the most common disorders associated with the occurrence and development of cataract, this review takes a broader look at this particular aspect, describing the relationship between cataracts and a group of genetic diseases. The links between cataracts and genetic diseases have been investigated. This review focuses on the diseases most frequently reported in the literature to be associated with cataracts, such as Down syndrome, myotonic dystrophy, neurofibromatosis type 2, Marfan syndrome, Wilson disease and Alport syndrome. The associations of cataracts with various genetic diseases, confirmed in previously published studies, were described. Despite the fact that it is difficult to distinguish individual factors influencing the development of cataract, the analyzed literature examples allowed to demonstrate that cataract in the course of the genetic disorders discussed in this review is not accidental.